Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project (University of Maribor Press, 2026)
This book presents an interdisciplinary synthesis of research findings from the Horizon Europe project SOLARIS. It systematically examines deepfake technologies as a structural threat to democratic institutions. Eight chapters integrate technological, psychometric, semiotic, legal, and political science perspectives, empirically analyzing both epistemic risks and potential positive applications of synthetic media. The authors critically examine generative neural network architectures, viral propagation mechanisms of disinformation in digital networks, and cognitive-affective factors in perceived trustworthiness of AI-generated content. The work identifies deepfake impacts on electoral integrity, epistemic erosion of public discourse, and asymmetric effects on marginalized populations. Critical evaluation of European regulatory instruments (AI Act, DSA) leads to formulation of innovative policy recommendations for systemic resilience of democratic processes. The research also documents positive implementations of synthetic media in pedagogical, cultural-documentary, and civic engagement contexts. This publication manily targets the research community, policymakers, media professionals, and technological actors.